Effect of Knowledge Acquisition on Academic Performance of Postgraduate Students of Private Universities in Kenya - Onditi , Walter Ouma; Murithi, Simon; Nzioki, Susan (International Journal of Professional Practice, 2022)
The concept of Knowledge Management (KM) has been used in measuring and gauging institutional performance. However, the effect of Knowledge Acquisition (KA) practices on academic performance of higher learning institutions is yet to be contextualized. This study attempted to bridge the aforementioned academic gap by assessing the effect of KA practices on academic performance on postgraduate students of private universities in Kenya, based on the theory of Resource Based View (RBV). Descriptive cross-sectional survey design was employed. A sample of 370 respondents was drawn from a population of 12,919 postgraduate students and faculty/department heads. Stratified random sampling technique was adopted in obtaining this sample. The findings established 27.8% variation in postgraduate academic performance; KA practice had very weak positive and insignificant correlation (r=0.044) and insignificant partial factor effect (β = 0.040, p=0.526) on postgraduate academic performance in private universities. The study concluded that KA did not have significant effect on postgraduate academic performance in private universities in emerging economies. Therefore, factors other than KM contributed to the academic performance, and they are worth exploring in future studies. The study recommends further research in methodologies and measures of knowledge acquisition as ways of improving application of knowledge management practices on students’ academic performance